(untitled) (Asian Journal of Medical and Biological Research, 2025)
Listeria monocytogenes is a potentially lethal foodborne pathogen responsible for listeriosis, a serious and often invasive multisystem disease. This pathogen can infect a wide range of host tissues, leading to various clinical outcomes, from febrile gastroenteritis to severe complications such as sepsis, meningitis, and spontaneous abortions. Recognized as a human pathogen for over 80 years, L. monocytogenes presents an increasing public health challenge, especially in light of rising use of immunosuppressive therapies for cancer and other conditions, which has intensified infection risk among vulnerable individuals and elevated listeriosis prevalence in communities. Additionally, shifts in consumer behavior, with reduced time spent on food preparation and greater reliance on ready-to-eat and convenience foods, have heightened exposure risks. Advances in food production and preservation technologies have led to extended shelf-life products, often associated with increased Listeria risk. Addressing L. monocytogenes requires collective efforts from consumers, public health authorities, and the food industry. For effective disease monitoring, health authorities must implement a robust screening program to detect listeriosis cases, alongside regular characterization of isolates from human, food, and environmental sources. Integrating these data into shared databases is essential for tracking the pathogen and enforcing preventive measures. Asian J. Med. Biol. Res. 2025, 11(1), 5-12